COMPARATIVE ANALYSIS: STUDENT ENTREPRENEURSHIP INTEREST - Adila Tsabita Suryo Kusumo; Dika Damayanti; Shelomita Candra Herdiana; Nur Septi Naily Karima; Fatmah Bagis (Proceeding International Seminar of Islamic Studies, 2023)
Planned Behavior Theory (SDGs) was used in this study to determine the role of attitudes towards entrepreneurial interests. The respondents used for analysis were students from one of the universities in Purwokerto totaling 341 people from a total population of 2500 students. PLS analysis is used to determine the influence of attitudes on entrepreneurial interest while the t-test is used to find out the differences before students take entrepreneurship lectures and after attending lectures. The results showed that the results of the analysis for attitudes towards entrepreneurial interest from the first analysis and the second analysis showed differences. As for the t-test, the results were obtained that entrepreneurship lectures have a significant impact on students' interest in entrepreneurship.